The Influence of Holistic Intelligence on Excellency of From Six Students in Sabah - Mohd Nasir Rayung; Abdul Said Ambotang; Mohd Yusof Abdullah (2018)
This descriptive study aims to determine the influence of holistic intelligence (HQ) through intellectual intelligence (IQ), physical intelligence (PQ), emotional intelligence (EQ) and spiritual intelligence (SQ) on student outcome (SO). Assessment was made to Form Six students as a subject based on gender, course, race and school category. Samples of the study consisted of 418 students from fifteen schools randomly selected using a randomized sampling method. This research instrument contains 84 items modified from the 4IR-Intelligence Instrument, Standard Quality of Malaysia Education (SKPM), California Critical Disposition Inventory-test (CCDI), and Ethical Reasoning Tool (ERT). The data were analyzed using Statistical Packages for Social Sciences (SPSS) and Structural Equation Modeling Analysis (SEM). The findings showed that IQ, PQ, EQ and SQ variables have positively correlated with SO variables. Findings also indicate that IQ, PQ, EQ and SQ was good predictors for student outcome (SO). All these findings tested at the confidence level of p<0.05. This study suggested that student holistic intelligence can be enhanced to ensure the student identity in line with the need of the nation in the future.